So close yet so unequal: Reconsidering spatial inequality in U.S. cities - Francesco Andreoli; Eugenio Peluso (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2017)
Spatial income inequality in cities is assessed by looking at the distribution of income across individuals and their neighbors. Two new Gini-type spatial inequality indices are introduced: the first index measures the average degree of income inequality within individual neighborhoods; the second index measures the inequality of average incomes among individual neighborhoods. Connections with geostatistics are investigated and the asymptotic distributions of these indices are derived. A rich income database from the U.S. census is used to establish new stylized facts about the patterns of spatial inequality in the 50 largest American cities during the last 35 years. Four different types of city are identified, according to the level of inequality between and within individual neighborhoods. Inequality within the neighborhood is shown to be associated with lifelong economic and health expectations of urban residents.
Keywords: C34; D31; H24; P25; 330; Neighborhood inequality; Gini; individual neighborhood; variogram; geostatistics; census; ACS; causal neighborhood effects; life expectancy; divided city; mixed city